The importance of child car seat safety - Tawfeeq A. Khoja (19772931) (2015)
Provoking the loss of a productive workforce and the waste of economic resources, through death or disability, the social and economic ramifications of road accidents attract the attention of researchers and stakeholders alike. Accidents have detrimental social, health and psychological consequences for families and cause them financial burdens. One of the means of protection against road accidents lies in taking preventive safety measures and educating children about them in order to reduce the risk of exposing children to accidents in the Kingdom of Saudi Arabia. Excluding non-communicable diseases, road accidents are the leading cause of death in the Kingdom. The safety belt in the vehicle is the first means of safety while driving. The 1998 Saudi Law on the use of safety belts defines the device as that part which holds the user's body firmly on the seat. On account of the exponential increase in the rate of road accidents and casualties, the need for the use of seatbelts cannot be overemphasized. This does not exclusively concern adults but also children who should be provided with the necessary means of protection and safety. Other Information Published in: Journal of Local and Global Health Science, title discontinued as of (2017) License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/jlghs.2015.itma.106